Насіннєва продуктивність та біологія проростання насіння видів роду Allium L. флори Північного Причорномор'я - Martsenyuk, I.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The biology of germination of seed and seminal productivity of five species of genus Allium L. of natural flora in the North of the Black Sea region was studied. It is discovered that by an optimum temperature for germination of seeds, of A. waldsteinii G. Don., A. rotundum L. and A. guttatum Stev. there is 20 °C, but for A. flavescens Bess. and A. paniculatum L. it is a range of low temperatures (10–15 °C). Fresh-collect seeds are characterized shallow physiology quiet which is violated during storage or cold stratification of seeds. All species were characterized by the low real productivity of seeds (lower than 50%). The highest productivity had A. flavescens (49.3%), the lowest – A. guttatum (32.9%).